Antitumor Mechanisms of Lycium barbarum Fruit: An Overview of In Vitro and In Vivo Potential - Maria Rosaria Miranda; Vincenzo Vestuto; Giuseppina Amodio; Michele Manfra; Giacomo Pepe; Pietro Campiglia (Life, 2024)
Lycium barbarum, known as goji berry or wolfberry, is a fruit long associated with health benefits, showing a plethora of effects ranging from antioxidant, anticancer, anti-inflammatory, and immunomodulatory effects. Its potential is attributed to the significant presence of polysaccharides, glycopeptides, polyphenols, flavonoids, carotenoids, and their derivatives. These compounds effectively counteract the action of free radicals, positively influencing cellular balance and intracellular signaling, contributing to overall cell health and function acting on multiple molecular pathways. Several fractions extracted from goji berries demonstrate antitumor properties, particularly effective against breast cancer, without showing cytotoxic effects on normal human cells. Hence, the review explored the fundamental traits of bioactive elements in Lycium barbarum and their potential in cancer treatment and, specifically, breast cancer. It focused on elucidating wolfberry’s influenced biochemical pathways, its synergism with anticancer drugs, and its potential to alleviate the side effects associated with existing cancer treatments.